Effects of dexmedetomidine on the expression of inflammatory factors in children with congenital heart disease undergoing intraoperative cardiopulmonary bypass: a randomized controlled trial - Yongsheng Qiu; Chan Li; Xiaoqin Li; Yingping Jia (Wiley, 2020)
Abstract Importance Dexmedetomidine inhibits the inflammatory response associated with cardiopulmonary bypass (CPB) and protects neural function. However, the mechanism of dexmedetomidine's anti‐inflammatory pathway is unclear. Objective To investigate the effect of dexmedetomidine on the cognitive level and expression of inflammatory factors in children with congenital heart disease undergoing intraoperative CPB. Methods Ninety children with congenital heart disease were recruited and randomly divided into 3 groups of 30 children in each. In Group 1, a 1.0 µg·kg‐1·h‐1 intravenous bolus of dexmedetomidine was administered 10 minutes after induction of anesthesia, followed by a 0.2 µg·kg‐1·h‐1 infusion until the surgical incision. In Group 2, a 0.5 µg/kg intravenous bolus of dexmedetomidine was administered 10 minutes after induction of anesthesia, followed by a 0.1 µg·kg‐1·h‐1 infusion until the surgical incision. The control group was given physiological saline using the same method as in Groups 1 and 2. The serum levels of nuclear factor‐kappa B (NF‐κB), S‐100β protein, neuron‐specific enolase (NSE), tumor necrosis factor‐α (TNF‐α), and interleukin‐6 (IL‐6) were measured before the surgery (T1), at the end of CPB (T2), 2 hours after CPB (T3), 6 hours after CPB (T4), and 24 hours after CPB (T5). The Wechsler Intelligence Scale for children (WISC) was measured before the operation and at 3, 6, and 12 months after the operation to evaluate the neurodevelopmental state of the children. Results The levels of the NF‐κB, S‐100β protein, NSE, TNF‐α, IL‐6 were significantly higher at T2, T3, or T4 than before the surgery (T1) in the control group or the dexmedetomidine groups. However, the increases of NF‐κB, TNF‐α, IL‐6, S‐100β and NSE levels were significantly smaller in the dexmedetomidine groups than those in the control group (P < 0.017). The WISC scores were similar among the three groups before or after the operation. Interpretation The increases in NF‐κB, TNF‐α, and IL‐6 levels indicated aggravation of the inflammatory reaction and the increase S‐100β protein and NSE levels indicated that the nervous system was damaged. Administration of dexmedetomidine to children with congenital heart disease undergoing intraoperative CPB can inhibit the inflammatory response and may ameliorate the neurodevelopmental damage caused by CPB.